The lysosomal TRPML1 channel regulates triple negative breast cancer development by promoting mTORC1 and purinergic signaling pathways. (May 2019) - Xu, Mengnan; Almasi, Shekoufeh; Yang, Yiming; Yan, Chi; Sterea, Andra Mihaela; Rizvi Syeda, Alia Kazim; Shen, Bing; Richard Derek, Clements; Huang, Peng; Gujar, Shashi; Wang, Jun; Zong, Wei-Xing; et al.
Graphical abstract: Highlights: TRPML1 is specifically upregulated in triple-negative breast cancers (TNBCs). Downregulation and pharmacological inhibition suppress the growth of TNBCs. TRPML1 regulates TNBC development through controlling mTORC1 activity and lysosomal ATP release. Abstract: The triple-negative breast cancer (TNBC) that comprises approximately 10%–20% of breast cancers is an aggressive subtype lacking effective therapeutics. Among various signaling pathways, mTORC1 and purinergic signals have emerged as potentially fruitful targets for clinical therapy of TNBC. Unfortunately, drugs targeting these signaling pathways do not successfully inhibit the progression of TNBC, partially due to the fact that these signaling pathways are essential for the function of all types of cells. In this study, we report that TRPML1 is specifically upregulated in TNBCs and that its genetic downregulation and pharmacological inhibition suppress the growth of TNBC. Mechanistically, we demonstrate that TRPML1 regulates TNBC development, at least partially, through controlling mTORC1 activity and the release of lysosomal ATP. Because TRPML1 is specifically activated by cellular stresses found in tumor microenvironments, antagonists of TRPML1 could represent anticancer drugs with enhanced specificity and potency. Our findings are expected to have a major impact on drug targeting of TNBCs.